Utilization of Black Tiger Shrimp Flesh Waste for Pop Shrimp Processing - Hari Eko Irianto; Dian Dwi Putri; Siti Zahro Nurbani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
A study on the utilization of black  tiger shrimp (Penaeus monodon) flesh waste in the processing of pop shrimp has been carried out.  So far, shrimp flesh waste is used for the production of shrimp paste, and shrimp cracker.   The objective of this study was to develop a fomula for pop shrimp production using shrimp flesh waste. Experimental design applied in this study was three-variables mixture design, in which variables observed were shrimp flesh waste, surimi and tapioca flour. Pop shrimp obtained was evaluated for sensory properties. The best product processed using a selected formula was analysed chemically and microbiologically, particularly for proxymate composition and total plate count respectively. Selected formula of pop shrimp consisted of 50.91% shrimp flesh waste, 18.18% surimi, 3.64% tapioca flour, 10.91% onion, 2.18% garlic, 0.73% pepper powder, 1.45% sugar, 0.36% monosodium glutamate, 0.73% ginger, 1.45% salt, 4.44% butter mix, 1.38% corn flour (maizena) and 3.64% bread crumb. Proxymate composition of the best pop shrimp was 70.52% moisture, 0.73% ash, 0.39% fat, and 7.44% protein, while microbiological load in terms of total plate count was 3.3x103 colonies/g.